New Users and Changing Traditions—(Re)Defining Sami Offering Sites - Äikäs, Tiina; Spangen, Marte (European Journal of Archaeology, 2016)
Sami are indigenous people of Northern Fennoscandia. Some Sami offering sites have been used for over a thousand years. During this time, the offering traditions have changed and various people have started using the places based on different motivations. Present day archaeological finds give evidence of both continuing traditions and new meanings attached to these sites, as well as to sites that were probably not originally used for rituals in the Sami ethnic religion. In some cases, the authenticity of the place seems to lie in the stories and current beliefs more than in a historical continuity or any specifically sacred aspects of the topography or nature it is situated in. Today's new users include, for example, local (Sami) people, tourists, and neo-pagans. This paper discusses what informs these users, what identifies certain locations as offering sites, and what current users believe their relationship to these places should be. What roles do scholarly traditions, heritage tourism, and internal culture have in (re)defining Sami offering sites and similarly what roles do ‘appropriate’ rituals have in ascribing meaning to particular places? How do we mediate wishes for multivocality with our professional opinions when it comes to defining sacredness?